Does believing in different types of religion affect subjective wellbeing? Analysis of the public data of the Taiwan Social Change Survey - Ding, Yu; Huo, Weidong; Jin, Yaning (Frontiers in Psychology, 2022)
The enhancement of material living standards produced by economic development is usually regarded as an important factor in the subjective happiness of the public. Since the “Easterlin Paradox” was proposed, however, researchers have begun to pay more attention to the role of mental factors in subjective well-being. In particular, the relationship between religious belief and subjective well-being has increasingly become a focus of research. Based on this, the goal of this paper is to reveal the underlying mechanism by which the type of religiosity affects residents' subjective well-being using a quantitative research method. By adopting public data from the Taiwan Social Change Survey, this study finds an indirect correlation between the type of religious belief and subjective well-being that is fully mediated by the frequency of participating in religious activities based on an empirical test of the mediation model. Specifically, the discrepancy in the frequency of participation in religious activity caused by different types of religious belief changes personal well-being. Respondents who adhere to institutional religion have a higher frequency of participating in religious activities, which has a positive impact on subjective well-being. Moreover, further examination shows that urban‒rural areas play an important moderating role: respondents living in urban areas are more inclined to participate frequently in religious activities to gain a sense of well-being.